Selenium Yeast Alleviates Ochratoxin A-Induced Apoptosis and Oxidative Stress via Modulation of the PI3K/AKT and Nrf2/Keap1 Signaling Pathways in the Kidneys of Chickens. (20th February 2020) - Li, Kang; Cao, Zhongjun; Guo, Yang; Tong, Cui; Yang, Shuhua; Long, Miao; Li, Peng; He, Jianbin
Abstract : The purpose of this study was to investigate the protective effect and mechanism of yeast selenium (Se-Y) on ochratoxin- (OTA-) induced nephrotoxicity of chickens. A total of 80 one-day-old healthy chickens were randomly divided into 4 equal groups: control, OTA (50 μ g/kg OTA), Se-Y (0.4 mg/kg Se-Y), and OTA+Se-Y (50 μ g/kg OTA+0.4 mg/kg Se-Y). In the OTA chickens, differences in body weight, kidney coefficient, biochemical histological analysis, antioxidant capability, and the expression levels of the PI3K/AKT and Nrf2/Keap1 signaling pathway-related genes were observed. The levels of total superoxide dismutase (T-SOD), antioxidant capacity (T-AOC), catalase (CAT), and glutathione (T-GSH) significantly decreased, but the malondialdehyde (MDA) level of the kidneys significantly increased in the OTA treatment group. More importantly, treatment with Se-Y improved the antioxidant enzyme activities within the kidneys of chickens exposed to OTA. In addition, administration of OTA resulted in apoptosis and was associated with decreased expression of AKT, PI3K, and Bcl-2, which in turn enhanced expression of Caspase3, Bax, and P53. However, Se-Y improved the antioxidant defense system through activation of the Nrf2/Keap1 signaling pathway. Gene expression of Nrf2 and its target genes (HO-1, GSH-px, GLRX2, MnSOD, and CAT) was downregulated following OTA exposure. Conversely, Se-Y treatment resulted in a significant upregulation of the same genes. Besides, significant downregulations of protein expression of HO-1, CAT, MnSOD, Nrf2, and Bcl-2 and a significant upregulation of Caspase3 and Bax levels were observed after contaminated with OTA. Notably, OTA-induced apoptosis and oxidative damage in the kidney of chickens were reverted back to normal level in the OTA+Se-Y group. Taken together, the data suggest that Se-Y alleviates OTA-induced nephrotoxicity in chickens, possibly through the activation of the PI3K/AKT and Nrf2/Keap1 signaling pathways.